Seasonal variations in aerosol optical thickness over eastern China determined from VIIRS data and ground measurements. Issue 8 (17th April 2016) - Meng, F.; Xin, J. Y.; Cao, C. Y.; Shao, X.; Shan, B. Y.; Xiao, Q. F.
ABSTRACT: Two-year records of Visible Infrared Imaging Radiometer Suite (VIIRS) Intermediate Product (IP) data on aerosol optical thickness (AOT) at 550 nm were evaluated by comparing them to sun-sky radiometer measurements from the Chinese Sun Hazemeter Network (CSHNET) and the Aerosol Robotic Network (AERONET). The monthly and seasonal variations in the aerosol optical properties over eastern China were then investigated using collocated VIIRS IP data and CSHNET and AERONET measurements. Between 59.2 and 62.1% of the retrieved VIIR IP values fell within the range defined for MODIS (Moderate Resolution Imaging Spectroradiometer) and had similar values for the correlation coefficient (0.880–0.909). The performances of the current VIIRS IP AOT retrievals at the provisional stage were consistent with ground measurements. However, over urban areas, the VIIRS exhibits more scatter and therefore less precision than observed over marine and rural areas. Similar characteristics of seasonal and monthly variations were found among the measurements, though the observational methodologies were different, showing maxima in the summer and spring and minima in the winter and autumn. Although the intensities vary from season to season, the spatial AOT distribution patterns did not change. High-AOT centres were situated in the industrialized coastal regions of China and were related to the distribution of urban areas.